STUDI MORFOLOGI DAN ANALISIS KORELASI ANTAR KARAKTER KOMPONEN HASIL TANAMAN SEREH WANGI (Cymbopogon sp.) DALAM UPAYA PERBAIKAN PRODUKSI MINYAK - Djati Waluyo Djoar; Panut Sahari; Sugiyono Sugiyono (Caraka Tani: Journal of Sustainable Agriculture, 2012)
Study Morphology and Correlation Analysis Inter ComponenYield Caracter of Citronella (Cymbopogon citratus). Lemongrass isfamiliar in Indonesia as a cooking ingredient known as Lemongrass (Cymbopogon citratus). Citronella considered as a rare plant that most peopledo not recognize yet. There are two species of Citronella are known Citronella Lenabatu (Cymbopogon nardus) and Citronella Mahapengiri (Cymbopogon winterianus) which is an essential oil taken as a raw material tomake medicine and perfume. This research was conducted in BKPH Southern Lawu, RPH Watu kempul and consortium village of Sendang, district Jatipuro, Wonogiri on December 2010. The purpose of this research are to find morphology characteristic, yield of essential oil and the variety level of Citronella, that all used as the selection foundation to get a bit of blood. This research uses 30 samples/accessions based on Random Proportions. Observation is conducted on the characteristic of morphology and yield of essential oil, variety level is implemented based on the Cluster analysis with average linkage method. The results show that 24,90% variety of Citronella in the area is not too varied. This variation can be seen from the morphological characteristic, and the differences of yield of essential oil produced.Accessions 26 and accessions 24 have highest oil yield with 1.421% and1.25%. The two samples have similar in the morphology, which they have similar red to purple leaf color, similar in the minimum number of plants inone clump (50-100) and the tall of plant that not too high (150 cm-200 cm).Components of plant cintronella fragrant hat could be use as selection criteria including of low plant hight, shorter of leaf size, number of plants per hill slightly and Shorter of stem length.